2008
DOI: 10.1074/jbc.m804003200
|View full text |Cite
|
Sign up to set email alerts
|

The Crystal Structure of Thrombin-activable Fibrinolysis Inhibitor (TAFI) Provides the Structural Basis for Its Intrinsic Activity and the Short Half-life of TAFIa

Abstract: Mature thrombin-activable fibrinolysis inhibitor (TAFIa) is a highly unstable metallocarboxypeptidase that stabilizes blood clots by clipping C-terminal lysine residues from partially degraded fibrin. In accordance with its in vitro antifibrinolytic activity, animal studies have reported that inhibition of mature TAFI aids in the prevention of thrombosis. The level of TAFI activity is stringently regulated through (i) controlled proteolytic truncation of the zymogen (TAFI), generating the mature enzyme, TAFIa,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
48
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 34 publications
5
48
0
Order By: Relevance
“…Recent studies have shown that the structure of TAFI is indeed similar to that of procarboxypeptidase B, thus supporting the model (36,37).…”
Section: Discussionmentioning
confidence: 57%
“…Recent studies have shown that the structure of TAFI is indeed similar to that of procarboxypeptidase B, thus supporting the model (36,37).…”
Section: Discussionmentioning
confidence: 57%
“…Crystal Structure Solution of the TAFI-TCI Complex-The structure of TAFI-TCI was solved by Patterson search techniques, assaying several strategies and combination of searching models, which corresponded to 100% identical chemical species: bovine TAFIa, TCI, and the pro-domain of bovine TAFI (45,52). Unambiguous solutions were found for the mature enzyme moiety and the inhibitor, but not for the prodomain.…”
Section: Characterization Of the Tafi-tci Complex By Size Exclusion Cmentioning
confidence: 99%
“…The crystal structures of human and bovine TAFI revealed the molecular basis for the thermodynamic instability of the mature protease as compared with its related, but more robust pancreatic counterparts (44,45). Furthermore, the incentive for the intrinsic proteolytic activity of the protein was revealed.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Significantly, the position of the pro-peptide is rotated 12° away from the active site, exposing access to the catalytic residues. Another significant distinction is the lack of the corresponding salt bridge between Asp 41 and Arg 145 in TAFI [42]. These distinctions might explain the intrinsic activity of TAFI [11,12].…”
Section: Introductionmentioning
confidence: 99%